2008
DOI: 10.1007/s11249-007-9290-1
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Adhesion Excited Micro-vibrations

Abstract: Understanding the mechanism of ''rubbing'' noise and low-amplitude friction exited vibration generation in steady sliding can be helped by models describing the contact interactions. In the current article, we consider a simple microscopic contact model for surfaces in sliding, which is based on the adhesion theory of friction. In the proposed model, we consider that the formation and shearing of a junction contributes to a small change in the real contact area. The model incorporates random size and random sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Excitation can also be provided by a fluctuating adhesion force. This can happen when junctions are formed and sheared between the surfaces and is described in a previous paper [31] on the mechanism of adhesion excited micro-vibrations. While the energy loss mechanism is essentially the same, the input to the system is imposed displacement in the case of roughness excitation and imposed force, in the case of adhesion excitation.…”
Section: Notes On the Excitationmentioning
confidence: 93%
“…Excitation can also be provided by a fluctuating adhesion force. This can happen when junctions are formed and sheared between the surfaces and is described in a previous paper [31] on the mechanism of adhesion excited micro-vibrations. While the energy loss mechanism is essentially the same, the input to the system is imposed displacement in the case of roughness excitation and imposed force, in the case of adhesion excitation.…”
Section: Notes On the Excitationmentioning
confidence: 93%
“…As aforementioned, a large amount of studies regarding the free vibrational behaviors of beam-like microstructures can be found, but the excited vibration analyses of beam-like microstructures have not been investigated fully, and this is due to the lack of an excited vibration model containing intrinsic scale effects. Nevertheless, excited vibration is the main form of structural vibration in practical engineering [15]. With respect to a beam-like microstructure, it heavily depends on whether or not the intrinsic characteristic effects are taken into account, because the characteristic effects, such as the scale effect, cause changes in its lateral vibration.…”
Section: Introductionmentioning
confidence: 99%